Acute stress impairs children's sustained attention with increased vulnerability for children of mothers reporting higher parenting stress. Issue 4 (10th September 2019) - Roos, Leslie E.; Giuliano, Ryan J.; Beauchamp, Kathryn G.; Berkman, Elliot T.; Knight, Erik L.; Fisher, Philip A.
Abstract: Despite evidence that acute stress impairs attention in adults, there has been minimal research in children. Here, the effects of acute stress on Go/No‐go performance were examined in young children ( M age = 5.41 years). Given the critical role of the parent–child relationship to children's self‐regulatory development, the extent to which parenting stress predicts children's cognitive vulnerability to acute stress and autonomic reactivity was also investigated. A between‐groups design ( n =  58 stress, n =  26 control) was used with oversampling of the stressor‐exposed children to examine individual differences. The Parenting Stress Index and subscales were employed as a measure of parenting stress. Acute stress impaired children's sustained attention, but not inhibitory control. Higher parenting stress was associated with vulnerability to attentional impairment. Parenting distress was also positively associated with sympathetic reactivity to acute stress, but neither sympathetic nor parasympathetic reactivity was associated with attentional impairment. A conceptual model of pathways through which repetitive acute stress may contribute to self‐regulatory difficulties is presented, including the potential buffering role of caregivers.